Clinical drug interaction profile of idelalisib in healthy subjects - Jin, Feng; Robeson, Michelle; Zhou, Huafeng; Moyer, Candra; Wilbert, Sibylle; Murray, Bernard; Ramanathan, Srini (Journal of clinical pharmacology, 2015)
Idelalisib, a potent phosphatidylinositol-3-kinase delta (PI3Kδ) inhibitor, is metabolized primarily by aldehyde oxidase to form GS-563117 and to a lesser extent by cytochrome P450 (CYP) 3A and uridine 5'-diphospho-glucuronosyltransferase 1A4. In vitro, idelalisib inhibits P-glycoprotein (P-gp) and organic anion transporting polypeptides 1B1 and 1B3, and GS-563117 is a time-dependent CYP3A inhibitor. This study enrolled 24 healthy subjects and evaluated (1) the effect of idelalisib on the pharmacokinetics (PK) of digoxin, a P-gp probe substrate, rosuvastatin, a breast cancer resistance protein, and OATP1B1/OATP1B3 substrate, and midazolam, a CYP3A substrate; and (2) the effect of a strong inducer, rifampin, on idelalisib PK. On treatment, the most common clinical adverse events (AEs) were headache and pyrexia. Grade 3 transaminase increases were observed in 5 of 24 subjects and were reversible. Two subjects had serious AEs after treatment completion (grade 3 pyrexia and/or drug-induced liver injury). Idelalisib coadministration did not affect digoxin and rosuvastatin PK. Coadministration with idelalisib increased plasma exposures of midazolam (138% and 437% for maximum observed plasma concentration [Cmax ] and area under the plasma concentration-time curve from time 0 extrapolated to infinity [AUCinf ], respectively), consistent with the in vitro finding of CYP3A inhibition by GS-563117. Rifampin caused a substantial decrease in idelalisib (58% and 75%, Cmax and AUCinf , respectively) and GS-563117 exposures, indicating an enhanced contribution of CYP3A to idelalisib metabolism under a strongly induced state.